Fourier-transform infrared spectra combined with chemometrics and fatty acid composition for analysis of pumpkin seed oil blended into olive oil - Rohman, Abdul; Che Man, YB; Ahmad Fadzillah, Nurrulhidayah (Taylor & Francis, 2015)
Fourier-transform infrared spectra in combination with chemometrics and fatty acid composition were used to analyze pumpkin seed oil blended into extra virgin olive oil. Two multivariate calibrations, namely, partial least square and principle component regression were evaluated for quantification of pumpkin seed oil in extra virgin olive oil. The combined frequency regions of 3020–2995 and 1070–900 cm−1 were preferred for such quantification using partial least square model with coefficient of determination (R2) obtained of >0.99. The errors in partial least square calibration and validation models were of 0.166 and 1.32% (vol/vol), respectively. Discriminant analysis can successfully classify extra virgin olive oil and extra virgin olive oil blended with pumpkin seed oil. The change of oleic and linoleic acids due to the addition of pumpkin seed oil into extra virgin olive oil can be used for the identification of blending practice of pumpkin seed oil into extra virgin olive oil. The level of oleic acid was decreased with the increasing concentration of pumpkin seed oil with R2 of 0.946. In addition, the level of linoleic acid was increased with the increasing level of pumpkin seed oil addition with R2 of 0.978.